Dampak Pengabdian Kepada Masyarakat Terhadap Pengembangan Pariwisata: Studi Kasus di Bali, Indonesia - Annisa Rizkikaddhuhani; I Wayan Bratayasa (Pusat Kajian Pariwisata dan Publikasi Jurnal Sekolah Tinggi Pariwisata Mataram, 2023)
Community service has become an essential aspect of sustainable tourism development, especially in developing countries where tourism is a significant source of revenue. This study aims to examine the impact of community service on tourism development in Bali, Indonesia. Using a case study approach, data were collected from various sources, including interviews with tourism stakeholders, community leaders, and tourists. The findings show that community service initiatives have a positive impact on tourism development in Bali. These initiatives contribute to the improvement of local infrastructure, the preservation of cultural heritage, and the promotion of eco-tourism activities. Moreover, community service projects increase community involvement in tourism, enhance community pride and ownership, and foster a sense of responsibility towards sustainable tourism development